Updated peer review of the pesticide risk assessment of the active substance flumioxazin. (29th September 2020) - ,; Anastassiadou, Maria; Arena, Maria; Auteri, Domenica; Brancato, Alba; Bura, Laszlo; Carrasco Cabrera, Luis; Chaideftou, Eugenia; Chiusolo, Arianna; Crivellente, Federica; De Lentdecker, Chloe; Egsmose, Mark; et al.
Abstract: The conclusions of the EFSA following the peer review of the initial risk assessments carried out by the competent authority of the rapporteur Member State, the Czech Republic, for the pesticide active substance flumioxazin are reported. The context of the peer review was that required by Commission Regulation (EU) No 1141/2010 as amended by Commission Implementing Regulation (EU) No 380/2013. The conclusions were reached on the basis of the evaluation of the representative uses of flumioxazin as a herbicide on winter wheat and sunflower (pre‐ and post‐emergence). The conclusions were updated with regard to the endocrine‐disrupting properties. The reliable end points concluded as being appropriate for use in regulatory risk assessment, derived from the available studies and literature in the dossier peer reviewed, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.